Bioethics of public commenting: Manipulation, data risk, and public participation in E‐Rulemaking. (6th September 2021) - Beever, Jonathan; Taylor, Lakelyn E.
Abstract: Little scholarly attention has been given to the ethics of public commenting as part of the online federal rule‐making process. This essay argues the process of public commenting on federal regulations in the digital era threatens both the integrity of those regulations and the integrity of the individuals they are meant to protect. The ongoing risk is anonymous public commenting is open to manipulation. This risk is particularly salient for eRulemaking with implications for human subjects as was shown in the completed revision process to the Common Rule. Guarding against physical and informational harms requires at least some verification of the identities of public commenters. The burdens of verification access are outweighed by the benefits to authentic participation in e‐Rulemaking.